How much emollient and steroid cream do eczema patients use, and the link between depression and steroid cream use. (31st March 2020) - Choi, J.Y.; Dawe, R.; Ibbotson, S.; Fleming, C.; Doney, A.; Foerster, J.
Summary: Atopic dermatitis (AD), often known simply as eczema, is a widespread condition, affecting between 15‐25% of children and between 4‐7% of adults worldwide. AD causes dry and itchy skin, and for many is a life‐long affliction. AD varies enormously, fluctuating between mild and severe in many patients. Twice daily and generous application of moisturisers (called "emollients"), as well as steroid‐containing creams applied to inflamed skin areas, can help to treat AD. For this reason, guidelines recommend the use of a pint‐sized tub of emollients per week. However, it is unknown how much moisturiser and steroid creams patients actually use. In order to find this out, researchers from the U.K. analysed electronic pharmacy dispensing records, which show how much of a medication patients are using. The most important findings were as follows: First, most patients in fact only use tiny amounts of moisturisers ‐ less than a third of a standard toothpaste tube (17 gram), for what should cover their entire body twice daily. Second, the use of steroid creams does not, on the whole, exceed guideline recommendations, which is reassuring. Third, there is a strong association between the use of steroid creams and treatment for depression. Thus, the number of patients requiring regular antidepressant treatment is almost double among patients requiring high amounts of steroid creams (50 gram or more per month) compared to those using lower amounts. This finding confirms previous suggestions of a link between currently having depression and more severe AD. Importantly, the findings highlight an urgent need for increased use of moisturisers, and that mental health may impact more heavily than thought on AD severity. This is a summary of the study: Quantitative analysis of topical treatments in atopic dermatitis: unexpectedly low use of emollients and strong correlation of topical corticosteroid use both with depression and concurrent asthma